2008
DOI: 10.1038/mp.2008.18
|View full text |Cite
|
Sign up to set email alerts
|

Face–brain asymmetry in autism spectrum disorders

Abstract: The heterogeneity of autism spectrum disorders (ASDs) confounds attempts to identify causes and pathogenesis. Identifiable endophenotypes and reliable biomarkers within ASDs would help to focus molecular research and uncover genetic causes and developmental mechanisms. We used dense surface-modelling techniques to compare the facial morphology of 72 boys with ASD and 128 first-degree relatives to that of 254 unrelated controls. Patternmatching algorithms were able to discriminate between the faces of ASD boys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
3
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(130 citation statements)
references
References 28 publications
6
117
3
2
Order By: Relevance
“…1,2 Using highly sensitive models of facial morphology, it has been possible to detect subtle differences in atypical patients and inform genotype-phenotype studies. 3,4 Advanced molecular genetic techniques have established increasingly detailed correlations between genotype and phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Using highly sensitive models of facial morphology, it has been possible to detect subtle differences in atypical patients and inform genotype-phenotype studies. 3,4 Advanced molecular genetic techniques have established increasingly detailed correlations between genotype and phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Development of the structures of the upper facial third is strictly related to forebrain development, and alterations in orbital characteristics may derive from cerebral malformations in the embryonic and fetal period. 1,22 In the current study, the faces of 2 groups of subjects with DS (Italian white and North Sudanese) were imaged in 3 dimensions using computerized instruments, and the morphologic features of their orbital soft tissues were quantitatively analyzed using indirect, computerized anthropometry. Data were compared with values collected in normal, healthy individuals of the same age, sex, and ethnicity.…”
Section: Y7mentioning
confidence: 99%
“…25,26 Previously, studies using 3D DSMs of face shape have delineated common facial features in a range of neurodevelopmental conditions, often, in addition, establishing accurate discriminating characteristics or assisting the determination of phenotype-genotype correlations. [26][27][28][29][30][31][32][33][34] We have shown that DSMbased analysis provides a very accurate instrument for classifying faces or facial regions along the control-WHS spectrum. In addition, for the first time, we have used DSMs to construct mean face surfaces matched for age and size for fine-grained analysis of six individuals, so that subtle face shape differences can be related to the underlying genotype.…”
Section: Wolf-hirschhorn Syndrome (Whs; Omim 194190) Is a Contiguous mentioning
confidence: 99%